2015
DOI: 10.1016/j.agrformet.2015.08.268
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-specific variation in drought sensitivity in Abies spec. and its relation to wood density and growth traits

Abstract: Understanding drought sensitivity of tree species and its intra-specific variation is required to estimate the effects of climate change on forest productivity, carbon sequestration and tree mortality as well as to develop adaptive forest management measures. Here, we studied the variation of drought reaction of six European Abies species and ten provenances of Abies alba planted in the drought prone eastern Austria. Tree-ring and X-ray densitometry data were used to generate early- and latewood measures for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 65 publications
(74 reference statements)
5
64
3
1
Order By: Relevance
“…This could be the case for the southernmost studied tree populations located at the lowest elevations, which were most dependent on spring and early summer climate conditions. Tree species show adaptive features to increasing drought stress by adjusting their hydraulic system (e.g., leaf area to sapwood area ratio) and phenology to local climate, particularly those most widespread as Scots pine (Martínez‐Vilalta et al ., ) and silver fir (George et al ., ). Our modeling approach could help to highlight locally adapted populations with traits providing drought tolerance and to derive predictions on future dieback events by mapping growth vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the case for the southernmost studied tree populations located at the lowest elevations, which were most dependent on spring and early summer climate conditions. Tree species show adaptive features to increasing drought stress by adjusting their hydraulic system (e.g., leaf area to sapwood area ratio) and phenology to local climate, particularly those most widespread as Scots pine (Martínez‐Vilalta et al ., ) and silver fir (George et al ., ). Our modeling approach could help to highlight locally adapted populations with traits providing drought tolerance and to derive predictions on future dieback events by mapping growth vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Provenance trials have confirmed that spruce grows on a wide range of site conditions. Provenances that are tolerant towards warm and dry In addition, Silver fir is seen as option at sites that are unsuitable for Norway spruce (Kapeller et al 2012;George et al 2015).…”
Section: Secondary Spruce In Central Europe-vulnerable Forests Requirmentioning
confidence: 99%
“…Adverse climatic conditions, mainly related to severe soil water deficit, may modify growth patterns and thus enhance the level of synchronicity among trees and provenances [14,15]. However, even if among-provenance differences in drought reaction are noticeable, these relationships may be temporally unstable, suggesting the phenotypic instability of provenances and/or the modifying effect of non-climatic factors [16,17]. Temporal instability in climate-growth relationships has been mainly observed in natural populations of forest trees [18][19][20][21], indicating at least two causal factors-current and past climate instability-as well as age-related trends in radial growth dynamics [22][23][24].…”
Section: Introductionmentioning
confidence: 99%